(untitled) (Journal of the College of Education for Women, 2018)
Pragmatics looked at literary discourse as an external subject that needed an actor and based on a communicative relationship, that is, it examines literary work by focusing on the author’s intent, and attempting to monitor the pilgrim and logical dimension in the text. It focuses on the practical and communicative aspect of the language, which aims to convince the recipient and his or her emotional influence.And the novel (Yamrim) starting from the title (Sos) communication, and building dialogue and pilgrims based on two different logic completely, the logic of optimism and look at things with absolute objectivity, the logic of pessimism and closure and look at things with absolute passion. These two tendencies are embodied by the characters Joseph and Maha, who have the task of recounting most of the events of the novel.The researchers adopted the deliberative approach in the study of the novel through reading semantics and meanings, temporal and spatial indications and aids, and monitoring of interferences, dialogues and the pilgrim dimension, reference references to the writer’s destination and text, as well as the use of descriptive analytic methods. It was incumbent on us to present a theoretical framework for the concept of the deliberative approach and a brief presentation of its origin and development, and its applicability to the narrative text, which is included in the first part of the research.